Fully Coupled FE Analyses of Buried Structures - James T. Baylot (Shock and Vibration)
Current procedures for determining the response of buried structures to the effects of the detonation of buried high explosives recommend decoupling the free-field stress analysis from the structure response analysis. A fully coupled (explosive–soil structure) finite element analysis procedure was developed so that the accuracies of current decoupling procedures could be evaluated. Comparisons of the results of analyses performed using this procedure with scale-model experiments indicate that this finite element procedure can be used to effectively evaluate the accuracies of the methods currently being used to decouple the free-field stress analysis from the structure response analysis.